School choice, school switching, and optimal assignment - Hessel Oosterbeek; Tina Rozsos; Bas van der Klaauw (Tinbergen Institute, 2025)
Close to 20% of secondary school students in Amsterdam - and elsewhere - transfer between secondary schools at some point, even when initially placed in their most-preferred school. School switching is costly for the students involved and disrupts the learning environment of their former and new classmates. Using data from the Amsterdam secondary-school match linked to administrative registers, we show that switching can be predicted by hard-torationalize initial school choices. Over 60% of switchers can be correctly identified at the admission stage. Simulations indicate that encouraging predicted switchers to adjust their preference ranking of schools could reduce the switching rate by almost 15%.
Keywords: I21; C35; C53; 330; secondary education; school choice; school switching; admission lottery